Sexual and reproductive health knowledge among primary school students in Malaysia - Shih-Hui Lee; Kee-Jiar Yeo (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: There is limited research on sexual and reproductive health (SRH) knowledge level among very young adolescents aged between 10 and 14 years. Policy makers and educators are unable to address very young adolescents' SRH needs without proper understanding of their SRH knowledge. Thus, the objective of this study is to explore very young adolescents' SRH knowledge level and the influences of demographic variables on the respondents' SRH knowledge level in Malaysian primary schools. MATERIALS AND METHODS: This cross-sectional study involved 617 primary five students who were recruited through multistage sampling method from the state of Johor, Malaysia. A self-administered questionnaire (Cronbach's α = 0.81) which comprised of 38 items related to puberty, HIV/AIDS and sexually transmitted diseases, prevention of child sexual abuse and reproductive systems and reproduction was used. Multivariate logistic regression analysis was applied to examine the association between demographic variables and student's SRH knowledge. RESULTS: Based on the results, 28.5% of the respondents had unsatisfactory level of SRH knowledge. Among the four dimensions, the respondents had more knowledge on prevention of child sexual abuse but displayed poorer knowledge on HIV/AIDS and sexually transmitted diseases topic. The findings indicated female (odd ratio [OR] = 1.464) and Indian respondents (OR = 3.208) are more likely to exhibit poor SRH knowledge which suggested demographic factors exert some extent of influence on primary school children's SRH knowledge. CONCLUSION: The findings provide useful insights for the policy makers and educators seeking to improve the comprehensiveness of culturally accepted sexuality education which are essential in promoting young adolescents' well-being.